2019
DOI: 10.1002/cctc.201901569
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Hydrothermal Synthesis of 1T@2H−MoS2 as an Excellent Photocatalyst

Abstract: In this work, a novel microwave hydrothermal method is developed to prepare hybrid 1T@2HÀ MoS 2 nanospheres, with the 1T and 2H phases confirmed by high-resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS) and the stability of the hybrid phase verified by Raman spectroscopy. The efficiencies of methyl orange (MO) degradation and photo-reduction of Cr(VI) by hybrid 1T@2HÀ MoS 2 are much higher than those by 2HÀ MoS 2 , which should be attributed to the synergistic effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…1j show a clear trigonal lattice region with a crystalline space of 0.27 nm assigned to the (100) plane of 1T-MoS 2 and a hexagonal region with a crystalline spacing of 0.30 nm attributed to the (100) plane of 2H-MoS 2 . 43 The flower-like morphology and conductive 1T phase are supposed to enhance the surface area and avail more active sites for the reaction, which will enhance H 2 S electrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…1j show a clear trigonal lattice region with a crystalline space of 0.27 nm assigned to the (100) plane of 1T-MoS 2 and a hexagonal region with a crystalline spacing of 0.30 nm attributed to the (100) plane of 2H-MoS 2 . 43 The flower-like morphology and conductive 1T phase are supposed to enhance the surface area and avail more active sites for the reaction, which will enhance H 2 S electrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…In the inset of Figure d, it can be observed that there are defects in the material (marked with white arrows), which may be related to the existence of sulfur vacancies, originating from the incorporation of Mn and/or the existence of the MoS 2 phase . In addition, the presence of two atomic structures in high-resolution TEM analysis is commendable: the interplanar crystal spacing of 0.27 nm can be allocated to the (100) plane of 1T phase MoS 2 , and the interplanar distance of 0.30 nm can be allocated to the (100) plane of 2H phase MoS 2 , which are in accordance with the results of XRD. EDX elemental mapping was performed on the above samples (Figure S5), and the test results confirmed the uniform distribution of elements in the composite material.…”
Section: Resultsmentioning
confidence: 99%
“…[ 293 ] From the views of optimisms, it is this process which endows them with high conductivity and abundant active sites. Though they lost their private offices for photocatalytic HER, they could still dedicate to this career by waltzing with those professional photon‐hunters as cocatalysts, thus many typical photosensitizers are on the cooperator list, including TiO 2 , [ 294 ] g‐C 3 N 4 , [ 295,296 ] CdS, [ 15 ] and their 2H phase counterparts, [ 297,298 ] and their corresponding performances are recorded in Table 7 . Besides serving as the electron suppliers, those semiconductors could also act as the one‐way streets for electrons to effectively reduce the number of backward electrons by forming metal–semiconductor Schottky junctions, [ 299 ] which could significantly lower the charge recombination rates and hence improve the catalytic kinetics.…”
Section: Energy Applicationsmentioning
confidence: 99%
“…[293] From the views of optimisms, it is this process which endows them with high conductivity and abundant active sites. Though they lost their private offices for photocatalytic HER, they could still dedicate to this career by waltzing with those professional photon-hunters as cocatalysts, thus many typical photosensitizers are on the cooperator list, including TiO 2 , [294] g-C 3 N 4 , [295,296] CdS, [15] and their 2H phase counterparts, [297,298] and their corresponding performances are recorded in Table 7.…”
Section: Photocatalytic Hydrogen Evolution Reactionmentioning
confidence: 99%